Pengaruh sistem informasi akuntansi dan sistem pengendalian internal terhadap kinerja karyawan - Wijaya, Dimas Azharino; Priono, Hero (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
The implementation of the internal control system at the Perumda BPR Bank Daerah Lamongan often results in weaknesses such as delays and input errors. Therefore, the need for an accounting information system and an internal control system is a system that has the task of managing financial data or transactions into information in the form of financial reports, the financial information is needed to meet the needs of internal and external parties that will be used as financial decision making. Implementation of Enterprise Resource Planning (ERP) can run smoothly, companies must prepare several things, including how to choose an ERP system that suits their needs, build a business model and prepare company management that must be carried out due to the implementation of the ERP system. The information system used in the company takes time to adapt for employees to operate it. This study aims to obtain empirical evidence of the effect of internal control systems and accounting information systems on employee performance. The object of this research is Perumda BPR Bank Daerah Lamongan with the number of employees who can be used as respondents as many as 34 employees. The analysis technique for this research uses a smart Partial Least Square (PLS) 3.0 tool. Based on data analysis, it was found that the internal control system and accounting information system statistically had a positive and significant effect on employee performance.